Transformation of Tradition: Incorporating Technology to Transform Local Culture in the Form of Modern Sundanese Script - Agung Zainal Muttakin Raden (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2019)
Sundanese script is a system for writing Sundanese. The traditional writing system in Sundanese began in the 14th century until the 19th century. Sundanese script is related to cosmology that developed in Sundanese society. This research will review the role of technology in transforming local values by comparing the Ancient Sundanese Script and the Modern Sundanese Script through ATUMICS method. The result of this study shows that there is a simplification happening when transforming the Ancient Sundanese Script to the Modern ones. However, the Sundanese cosmology embodied within the Sundanese script is not lost. Thus, transformation of tradition could become one of the options in preserving local traditional values while adapting it into the current world.